Select the correct difference.
5d2 + 4d - 3 less 2d2 - 3d + 4

Question

Asked 1/16/2015 10:38:11 AM

Updated 1/16/2015 5:29:42 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Flagged by janezeshun [1/16/2015 5:18:59 PM], Edited by andrewpallarca [1/16/2015 5:29:40 PM], Unflagged by andrewpallarca [1/16/2015 5:29:41 PM], Confirmed by andrewpallarca [1/16/2015 5:29:42 PM]

s

= 3d^2 + 7d - 7

= m - [n - (p + m + n - p)]

= m - [n - (m + n)]

= m - (n - m - n)

= m - (-m)

= m + m

= 2m

Question

Asked 1/16/2015 10:38:11 AM

Updated 1/16/2015 5:29:42 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Flagged by janezeshun [1/16/2015 5:18:59 PM], Edited by andrewpallarca [1/16/2015 5:29:40 PM], Unflagged by andrewpallarca [1/16/2015 5:29:41 PM], Confirmed by andrewpallarca [1/16/2015 5:29:42 PM]

Rating

3

-3z^7 - (-5z^7)

= -3z^7 + 5z^7

= 2z^7

= -3z^7 + 5z^7

= 2z^7

Added 1/16/2015 5:18:47 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [1/16/2015 5:29:50 PM]

(n + 8)(n - 2)

Question

Updated 1/16/2015 11:23:52 AM

1 Answer/Comment

(n + 8)(n - 2)

= n^2 - 2n + 8n - 16;

= n^2 + 6n - 16

= n^2 - 2n + 8n - 16;

= n^2 + 6n - 16

Added 1/16/2015 11:23:52 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [1/16/2015 11:32:00 AM]

x3y3 **Weegy:** Please be more specific with your question. **User:** Simplify -3p3 + 5p + (-2p2) + (-4) - 12p + 5 - (-8p3) **Weegy:** Please state your questions.
**User:** 5m + 2n, n - 3m, and 7 - 3n (More)

Question

Updated 1/15/2015 6:02:40 PM

2 Answers/Comments

-3p^3 + 5p + (-2p^2) + (-4) - 12p + 5 - (-8p^3)

= -3p^3 + 8p^3 + 5p - 12p - 2p^2 - 4 + 5

= 5p^3 - 2p^2 - 7p + 1

= -3p^3 + 8p^3 + 5p - 12p - 2p^2 - 4 + 5

= 5p^3 - 2p^2 - 7p + 1

Added 1/15/2015 6:01:43 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [1/16/2015 11:42:25 AM]

5m + 2n + (n - 3m) + (7 - 3n)

= 5m + 2n + n - 3m + 7 - 3n

= 2m + 7

= 5m + 2n + n - 3m + 7 - 3n

= 2m + 7

Added 1/15/2015 6:02:40 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [1/16/2015 11:44:20 AM]

2ay2 + 5ay - 3a **Weegy:** 2ay^2 + 5ay - 3a
= a(2y^2 + 5y - 3)
= a(2y - 1)(y + 3) (More)

Question

Expert Answered

Updated 1/16/2015 10:19:30 AM

0 Answers/Comments

Choose the product.
-7p3(4p2 + 3p - 1)
**Weegy:** -7p3(4p2 3p - 1) = 7p3 - 84p6. Source: (More)

Question

Updated 1/16/2015 7:16:22 PM

1 Answer/Comment

-7p^3(4p^2 + 3p - 1)

= -7p^3*4p^2 - 7p^3*3p + 7p3

= -28p^5 - 21p^4 + 7p^3

= -7p^3*4p^2 - 7p^3*3p + 7p3

= -28p^5 - 21p^4 + 7p^3

Added 1/16/2015 7:16:22 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [1/17/2015 10:39:50 AM]

Factor -2bk2 + 6bk - 2b. **Weegy:** -2bk^2 + 6bk - 2b = -2b(k^2 - 3k + 1) (More)

Question

Updated 1/16/2015 12:10:20 PM

0 Answers/Comments

31,452,241

questions answered

denyang

$462.55

Hearts 10,159 Views 2,018,117 Streams 613

sujaysen

$376.30

Hearts 8,372 Views 2,031,680 Streams 648

Flora1988

$338.00

Hearts 7,442 Views 2,418,370 Streams 738

miyaka

$325.90

Hearts 6,879 Views 3,022,389 Streams 898

PeachyStream97

$317.05

Hearts 6,830 Views 1,047,983 Streams 318

sampi1890

$315.05

Hearts 6,746 Views 3,412,556 Streams 932

maydj

$314.30

Hearts 6,791 Views 2,684,404 Streams 773

phpmicro

$244.70

Hearts 5,045 Views 1,923,543 Streams 516

There are no comments.